A unique methylation pattern by a type I HsdM methyltransferase prepares for DpnI rare cutting sites in the Pseudomonas aeruginosa PAO1 genome. Issue 5 (13th March 2019) - Fischer, Sebastian; Römling, Ute; Tümmler, Burkhard
ABSTRACT: A physical genome map of Pseudomonas aeruginosa PAO1 had been constructed in the late 1980s by combinatorial SpeI/DpnI long-range restriction mapping. Whereas SpeI was known to cleave within the infrequent 5′-ACTAGT hexanucleotide, the rare recognition site 5′-G m6 ATC for the methylation-sensitive 4-cutter DpnI in the PAO1 genome remained elusive. Resequencing the PAO1 genome with the methylation-sensitive Single Molecule Real-Time (SMRT) sequencing technology identified DpnI to cleave the PAO1 genome at 15 palindromic GAC(N)6 G m6 ATC(N)6 GTC recognition sites with the central G m6 ATC palindrome to be methylated on both strands by the clone PAO1-specific type I HsdM superfamily methyltransferase M.PaePAOI (PA2735). Abstract : The rare-cutting restriction endonuclease DpnI recognizes G m6 ATC at the palindromic decamer GAC(N)6 G m6 ATC(N)6 GTC in the Pseudomonas aeruginosa PAO1 genome.